2022
DOI: 10.1097/gme.0000000000001913
|View full text |Cite
|
Sign up to set email alerts
|

The long-term association between bilateral oophorectomy and depression: a prospective cohort study

Abstract: Objective: Depression is a leading cause of disability globally and affects more women than men. Ovarian sex steroids are thought to modify depression risk in women and interventions such as bilateral oophorectomy that permanently change the sex steroid milieu may increase the risk of depression. This study aimed to investigate the associations between unilateral and bilateral oophorectomy and depression over a 25-year period (1993-2018) and whether this varied by age at oophorectomy or use of menopausal horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…1). (32)(33)(34)(35)(36)(37) At study entry, the included nurses completed a selfadministered questionnaire with information on lifestyle, selfreported height and weight, and previous and current use of HT. The self-reported HT use has previously been validated, and researchers found high to moderate sensitivity (78.4%) and specificity (98.4%) of self-reported use of HT compared with registration in the Danish Prescription Registry.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…1). (32)(33)(34)(35)(36)(37) At study entry, the included nurses completed a selfadministered questionnaire with information on lifestyle, selfreported height and weight, and previous and current use of HT. The self-reported HT use has previously been validated, and researchers found high to moderate sensitivity (78.4%) and specificity (98.4%) of self-reported use of HT compared with registration in the Danish Prescription Registry.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…Different studies have found that the patient’s age at the time of surgery, the type of surgery (uni- or bilateral), and additional extirpation of the uterus all modulate the risk of depressive symptoms. Thus, women who were younger at the time of surgery ( 25 ), in addition to women older than 51 years ( 26 ), were both found to exhibit a higher risk of affective symptoms, while an increased risk for depression (syndromic) and complaints in general health are registered in women subjected to the extirpation of the uterus and ovaries ( 27 ).…”
Section: Introductionmentioning
confidence: 99%